Efficacy and Maternal Comfort of Sequential versus Simultaneous Breast Expression by Mothers of Critically III Newborns - Özge Altun Köroğlu; Nazmiye Can; Başak Yıldız Atıkan; Sema Tanrıverdi; Mehmet Yalaz; Mete Akısü; Nilgün Kültürsay (Journal of Pediatric Research, 2017)
Aim: Expressed breast milk is beneficial for infants in neonatal intensive care unit (NICU) when direct breastfeeding is not possible. Breast expression with manual or electric breast pumps is promoted for the initiation and maintenance of lactation in this critical period. In this study, we aimed to compare the efficacy and maternal comfort of sequential versus simultaneous breast expression in newly delivered mothers whose infants were admitted to NICU. Materials and Methods: Thirty five mothers were followed prospectively for milk expression either sequentially (n=21, group 1) or simultaneously (n=14, group 2) with breast pumps for 10 days. The total amount of milk expressed per day and per each period was recorded together with the duration of breast expression. The mothers’ impressions about the easiness and comfort of the procedure, and their satisfaction with the amount of milk were evaluated with a questionnaire at the end of the study. Results: The amounts of expressed milk per day and per each expression period were similar in both groups. However, time spent for each expression period was significantly lower in the simultaneous breast expression group. Mothers in this group gave higher scores with regard to ease of use when compared to mothers in the sequential expression group (4.36±0.50 vs. 4.00±0.44, p=0.046). The mothers graded both methods with similar scores in all other parameters. Conclusion: Simultaneous breast expression is time saving while both simultaneous and sequential breast expression are similarly efficient for milk production, and both methods are helpful and tolerable in promoting breastfeeding for NICU mothers.